Community pharmacy - based smoking cessation interventions (CPSCI): barriers, facilitators, and needs for the development and implementation in Manila City - Aguda, Frances Ann J.; Banzuela, Eian Peter P.; Ayran, Charles Mandy G. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2024)
Despite the current laws and programs implemented in the Philippines, smoking prevalence is still high. Hence, there is a need for a wider implementation of smoking cessation interventions through utilizing community pharmacists. The study aimed to identify the facilitators, barriers, and needs to successfully develop and implement Community Pharmacy-based Smoking Cessation Interventions (CPSCI) based on the perceptions of community pharmacists and representatives of pharmacy organizations and the academe. A phenomenological qualitative study was conducted in Manila among community pharmacists (n=14) and representatives (n=4). Identified themes using NVivo 14 were mapped out using the Capability, Opportunity, Motivation – Behavior model and Theoretical Domains Framework to identify determinants of behavior change to facilitate the development of more tailored and effective recommendations for the development and implementation of CPSCI. Guided by these frameworks, recommendations were formulated according to the identified barriers, facilitators, and needs. Identified themes for barriers were connected to the domains of knowledge, behavioral regulation, social influence, environmental context and resources, reinforcement, intentions, beliefs about capabilities, and beliefs about consequences. Whereas themes identified as facilitators were related to knowledge, social influence, environmental context and resources, reinforcement, emotion, social/professional role and identity, optimism, and goals. Meanwhile, identified needs involved knowledge, behavioral regulation, social influence, environmental context and resources, reinforcement, social/professional role and identity, intentions, beliefs about capabilities, optimism, intentions, goals, and beliefs about consequences. Most of the identified themes were patient-centric dealing with how CPSCI would reach or impact the patient. Thus, the identified needs were connected to the identified barriers and facilitators which aimed to address, and to strengthen or take advantage of these, respectively. The main difference between the perspectives of the participants is that community pharmacists focused on how the development and implementation of CPSCI will affect them, and how their individual factors may affect its development and implementation. Hence, more domains were identified in the barriers and facilitators, since they will be the ones on the ground to implement CPSCI. Whereas for the representatives, more domains were identified in the needs since they provide a wider perspective looking at the whole picture as the decision makers and leaders for the development of CPSCI. Barriers, facilitators, and needs should be taken into consideration before developing and implementing CPSCI. With this, this study recommends having interventions related to Business Plan, Capacity Building, Information Dissemination, Interprofessional Collaboration, Involvement of Health Authorities and Organizations, Management Support, Patient Empowerment, Product Availability and Affordability, Priority Realignment, Program Monitoring and Evaluation, Policy and Regulation, Recognition, Research, Resources, Space, and Tools to Assist Implementation.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2024
Keywords: Smoking cessation -- Community Pharmacy Services. -- City of Manila (Philippines); Health promotion -- Pharmacies -- Philippines; Public health -- Tobacco use cessation -- City of Manila (Philippines)